Molecular dynamics folding simulation of β-hairpins from protein G - Ahmad Khairuddin, Nurulbahiyah (2012)
The structure and trajectories of the 41-56 β-hairpins from the protein G (PDB ID: 1GB1) has been studied using Molecular Dynamics (MD) simulation. The purpose of this project is to investigate the pathway of the folding process. The simulation was run at 325 K for 50ns. The linear chain of the protein sequence became completely folded to β-hairpin structure at nearly 40ns. There were 18 interactions of hydrogen Bonds involved in the model. The model was aligned to the Nuclear Magnetic Resonance (NMR) structure with the RMSD value of 3.05 Å for overall structure and 1.04 Å for the turning part. The values of RMSD showed the comparison of the model and the native structure.